Epoxy/graphene nanocomposites prepared by in-situ microwaving. (15th June 2021) - Naeem, Mohannad; Kuan, Hsu-Chiang; Michelmore, Andrew; Yu, Sirong; Mouritz, Adrian P.; Chelliah, Sanjay S.; Ma, Jun
Abstract: Many preparation methods reported for polymer/graphene nanocomposites are associated with graphene surface modification and consumption of organic solvents. A facile, green and novel approach has been developed in this study for preparation of epoxy/graphene nanocomposites. The approach involves microwaving a commercial graphene precursor and mechanically stirring to produce graphene platelets in a hot, liquid-state epoxy resin, eliminating the need for organic solvents and surfactants. The process created both single-layer graphene and graphene platelets of 4.17 ± 0.63 nm in thickness and 1.00–4.77 μm in lateral dimension. Most of the surface oxygenated groups survived in this process, and more importantly, the process grafted epoxy molecules with graphene platelets. A thin film of platelets displayed an electrical conductivity of 889 ± 141 S/cm. The platelets caused large improvements to the mechanical and functional properties of the epoxy, i.e. 175% increase in critical strain energy release rate at 1.03 vol% of graphene, 14.9% increase in Young's modulus at 1.55 vol%, a percolation threshold of electrical conductivity at 0.85 vol%, and a glass transition temperature increment from 85.4 to 100.0 °C at 1.03 vol%. The research clearly demonstrates the use of microwave radiation as an environmentally sustainable, low-cost and simple method for the development of polymer nanocomposites containing exfoliated and well-dispersed graphene platelets. Graphical abstract: Image 1 Highlights: A precursor was converted into graphene in epoxy by microwave treatment and shearing. AFM measurement showed thickness of 4.17 ± 0.63 nm, whereas monolayer graphene was found by TEM. The nanocomposite at 1.03 vol% of graphene exhibited a 175% increment of critical strain energy release rate. A percolation threshold of electrical conductivity was found at 0.85 vol%.